Effect of traditional Chinese medicine on Graves’ disease: a network meta-analysis - Yang, Zhuoshi; Zhao, Na; Li, Jinchuang; Wu, Zhouxin; Ma, Jian (Frontiers in Pharmacology, 2024)
Introduction:Graves' disease(GD)is the most common cause of hyperthyroidism and can affect multiple systems of the body.Currently,commonly-used treatment methods for GD have a series of shortcomings. In contrast,traditional Chinese medicine has been proven to be effective in inhibiting the progression of GD and is expected to become a key direction for the development of new drugs in the future.Therefore,a network meta-analysis was performed to compare the impacts of different traditional Chinese medicines on the curative effect,thyroid-stimulating hormone(TSH),free triiodothyronine(FT3),free thyroxine(FT4),thyroglobulin antibody(TGAb),thyroid peroxidase antibody(TPOAb)and thyrotropin receptor antibody(TRAb)in patients with GD. Methods:PubMed,Embase,Cochrane Library,Web of Science,WanFang,Weipu,and CNKI were searched for the randomized controlled trials of traditional Chinese medicine on GD patients up to December 19,2023.The quality of the included studies was evaluated regarding the risk of bias,and the data were analyzed by R software. Results:Thirty-five articles were included in the analysis,involving 2828 GD patients and traditional Chinese medicines including Bailing Capsule,Jinshuibao Capsule,Astragalus injection,Jiakangling Tablet,Jiakangling Capsule,Tripterygium Wilfordii,Sanjie Xiaoying Decoction,Prunella vulgaris(L.)Oral Liquid,Prunella vulgaris (L.)Granules,Xiehuo Xiaoying Recipe,Xiehuo Yangyin Powder,Yikang Pill and Yinjia Pellet.The results of network meta-analysis suggested that for GD patients,Bailing Capsule,Jiakangling Capsule,Tripterygium wilfordii,Prunella vulgaris(L.)Oral Liquid and Yinjia Pellet had better curative effect compared with Western medicine.Prunella vulgaris(L.)Granules and Yikang Pill could improve the TSH level.Prunella vulgaris(L.)Granules,Prunella vulgaris(L.)Oral Liquid and Yikang Pill could reduce FT3 level. Jiakangling Capsule,Prunella vulgaris(L.)Granules,Prunella vulgaris(L.)Oral Liquid and Yikang Pill could reduce the FT4 level.Prunella vulgaris(L.)Oral Liquid can reduce the level of TPOAb and TRAb. Besides,Yinjia Pellet was the most helpful in improving the curative effect.Yikang Pill could best improve TSH.Prunella vulgaris(L.)Granules had the best effect on reducing FT3.Prunella vulgaris(L.)Granules performed best in reducing FT4.Prunella vulgaris(L.)Oral Liquid had the most favorable effect on reducing TPOAb and TRAb. Conclusion:Based on the current research,it is safe to conclude that Chinese medicine can improve the curative effect and TSH level of patients with GD,and reduce the levels of FT3,FT4,TPOAb and TRAb. Besides,Yinjia Pellet is the most helpful in improving the curative effect.Yikang Pill can best improve TSH. Prunella vulgaris(L.)Granules have the best effect on reducing FT3.Prunella vulgaris (L.) Granules perform best in reducing FT4.Prunella vulgaris(L.)Oral Liquid has the most favorable effect on reducing TPOAb and TRAb.